Preparation of high-quality graphene oxide-carbon quantum dots composites and their application for electrochemical sensing of uric acid and ascorbic acid. (8th January 2021) - Ding, Ling; He, Huan; Zhou, Jin; Wang, Dini; Nian, Qiong; Li, Shiqian; Qian, Shihui; Li, Wenbing; Liu, Cui; Liang, Zhengyong
Abstract: Graphene oxide-quantum dots systems are emerging as a new class of materials that hold promise for biochemical sensing applications. In this paper, the eco-friendly carbon quantum dots (CQDs) are prepared with cheap and recyclable coke powders as carbon source. The graphene oxide-carbon quantum dots (GO-CQDs) composites are synthesized using graphene oxide as the conductive skeleton to load the CQDs by a one-step calcination method. The obtained GO-CQDs composites demonstrate the successful decoration of CQDs on GO nanosheets. The CQDs acting as spacers create gaps between GO sheets, resulting in a high surface area, which electively increases the electrolyte accessibility and electronic transmission. The electrocatalytic activity and reversibility of GO-CQDs composites can be effectively enhanced by tuning the mass ratio of GO to CQDs and the heating process. Furthermore, a highly sensitive and selective electrochemical sensor for determining uric acid (UA) and ascorbic acid (AA) was developed by modifying GO-CQDs composites onto a glassy carbon electrode. The results show that the linear range, minimum detection limit, and sensitivity of the GO-CQDs electrode for UA detection are 1–150 μ M, 0.01 μ M, and 2319.4 μ A mM −1 cm −2, respectively, and those for AA detection are 800–9000 μ M, 31.57 μ M, and 53.1 μ A mM −1 cm −2, respectively. The GO-CQDs are employed as the electrode materials for the serum and urine samples electrochemical sensing, the results indicate that the sensor can be used for the analysis of real biological samples.